Vocabulary Ability of University Students in Identify Nouns in Descriptive Texts from The Jakarta Post: An Analysis - Cici Situmorang; Hilwa Salsa Bilah; Lisda Tri Aurora; Sanija Sanija (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The paper focuses on the capabilities of students from the Prima Bangsa Institute to identify nouns from descriptive texts sourced from The Jakarta Post edition published on November 1, 2025. The approach of the study was qualitative descriptive, aided by instruments constructed in a multiple-choice tests and interviews.The multiple-choice test has the objective to identify the capabilities of students to identify and differentiate nouns according to their categories, including common nouns, proper nouns, abstract nouns, and collective nouns. Meanwhile, interviews could identify the problems encountered by learners during the learning process. Based on the average scores achieved, students' capabilities to identify nouns reached 56 and were under the category of fairly good. The most easily recognized noun for students was the common noun, while abstract nouns, proper nouns, and collective nouns were not yet fully understood by students. The problems were dominated by less mastery of students on English vocabulary and less mastery of understanding meanings of words based on context, especially when students encounter real texts for the first time. In light of the findings, this study underlines the significance of context-based vocabulary mastery of nouns to increase students' mastery of descriptive texts of the English language.